Local Businesses to Global Digital Presence: Building Authentic Online Identities among Small Businesses in Surakarta - Kyeyune Hamidu; Anton Agus Setyawan; Muhammad Sholahuddin; Ihwan Susila (Walidem Institute and Publishing, 2026)
Objective: This study examines how small batik businesses in Surakarta build authentic online identities while entering the global digital marketplace. Theoretical framework: Guided by the concept of Digitally Mediated Authenticity, the study explains how authenticity is created through digital communication, cultural storytelling, transparency, and customer engagement. Literature review: The study addresses the limited research on how cultural SMEs translate local heritage, craftsmanship, and brand authenticity into digital formats that global consumers can understand and trust. Method: A qualitative case study approach was employed using semi-structured interviews with nine informants representing batik businesses and related stakeholders. Data were analysed through thematic analysis to identify key patterns and themes. Results: The findings reveal four key practices for building authentic online identities: visual transparency, narrative grounding, interactive co-construction, and platform alignment. Export-oriented SMEs also rely on digital communication tools, although challenges remain in visibility, financial integration, and logistics. Implications: The study enriches the literature on brand authenticity, cultural branding, and SME digitalisation by demonstrating that authenticity is continuously negotiated and sustained through digital practices and trust-based relationships. Novelty: This research provides a new perspective on how cultural SMEs digitally construct and communicate authenticity in global markets. It highlights authenticity as a dynamic and digitally mediated process rather than a fixed organisational attribute.